A Girl with Autoimmune Cytopenias, Nonmalignant Lymphadenopathy, and Recurrent Infections - Marjolein A. C. Mattheij; Ellen J. H. Schatorjé; Eugenie F. A. Gemen; Lisette van de Corput; Peet T. G. A. Nooijen; Mirjam van der Burg; Esther de Vries (Case Reports in Immunology)
We describe a girl, now 9 years of age, with chronic idiopathic thrombocytopenic purpura, persistent nonmalignant lymphadenopathy, splenomegaly, recurrent infections, and autoimmune hemolytic anemia. Her symptoms partly fit the definitions of both autoimmune lymphoproliferative syndrome (ALPS) and common variable immunodeficiency disorders (CVIDs). Genetic analysis showed no abnormalities in the ALPS-genes FAS, FASLG, and CASP10. The CVID-associated TACI gene showed a homozygous polymorphism (Pro251Leu), which is found also in healthy controls.